1987
DOI: 10.1104/pp.83.4.795
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Growth Promoting Activities and Toxicities of Various Auxin Analogs on Cells Derived from Wild Type and a Nonrooting Mutant of Tobacco

Abstract: The aim of the present work was to further study the characteristics of stimulation of growth of wild type and mutant cells by various auxins. The ability of the mutant to form auxinconjugates was investigated as a possible basis for increased auxin tolerance. An auxin analog specifically triggering cell death was identified by differential screening on wild-type and mutant cells. MATERIALS AND METHODSAn auxin requirement for the stimulation of cell proliferation has been demonstrated for many types of tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Transmembrane potential measurements performed on the two genotype protoplasts showed a decreased ability of mutant protoplasts to respond to exogenously supplied auxin. This cellular characteristic of mutants is expected to be also expressed in tissues since mutant plantlets are more tolerant than wild-type plantlets to high auxin concentration (7). Thus, the mutation could disturb the biosynthesis of a possibly membrane-bound auxin receptor or could inactivate it.…”
Section: Iaa Levelsmentioning
confidence: 99%
“…Transmembrane potential measurements performed on the two genotype protoplasts showed a decreased ability of mutant protoplasts to respond to exogenously supplied auxin. This cellular characteristic of mutants is expected to be also expressed in tissues since mutant plantlets are more tolerant than wild-type plantlets to high auxin concentration (7). Thus, the mutation could disturb the biosynthesis of a possibly membrane-bound auxin receptor or could inactivate it.…”
Section: Iaa Levelsmentioning
confidence: 99%
“…Recently, Korber et al (17) have demonstrated that the gene 5 product converts tryptophan into indole-3-lactate, which is an auxin antagonist. These authors suggested that the gene 5 product plays a role in fine tuning the auxin/cytokinin ratios in crown gall tissue. It is thus not inconceivable to propose that gene 5 expression would respond directly to auxins and cytokinins.…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggested that the gene 5 product plays a role in fine tuning the auxin/cytokinin ratios in crown gall tissue. It is thus not inconceivable to propose that gene 5 expression would respond directly to auxins and cytokinins. However, we cannot exclude that some other natural compounds, which have no structural homologies with the classical auxins and cytokinins, also have activity in our bioassay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our overall hypothesis is that adventitious rooting competence in cuttings has a molecular basis at the leve1 of auxinregulated gene expression in phloem parenchyma or inner cortical parenchyma cells during adventitious root initiation. In an attempt to identify genes that are specifically regulated during auxin-induced adventitious root initiation, we compared gene expression in cuttings from shoots of adventitious rooting-competent wild-type tobacco (Nicotiana tabacum cv Xanthii) with the rooting-incompetent rac mutant (Muller et al, 1985;Caboche et al, 1987;Pelese et al, 1989;Barbier-Brygoo et al, 1991).…”
mentioning
confidence: 99%